Active Matrix Flat Panel Bio-Medical X-ray Imagers - Lai, Jackson (University of Waterloo, 2008)
This work investigates the design, system integration, optimization, and evaluation of amorphous silicon (a-Si:H) active matrix flat panel imagers (AMFPI) for bio-medical applications. Here, two hybrid active pixel sensor (H-APS) designs are introduced that improve the dynamic range while maintaining the desirable attributes of high speed and low noise readout. Also presented is a systematic approach for noise analysis of thin film transistors (TFT) and pixel circuits in which circuit analysis techniques and TFT noise models are combined to evaluate circuit noise performance. We also explore different options of system integration and present measurement results of a high fill-factor (HFF) array with segmented photodiode.
Keywords: X-ray imaging; Active Matrix Panel; Amorphous Silicon Technology; Electrical and Computer Engineering